Starvation avoidance-based dynamic multichannel access for low priority traffics in 802.11ac communication systems. (March 2021) - Mammeri, Souhila; Yazid, Mohand; Kacimi, Rahim; Bouallouche-Medjkoune, Louiza
Abstract: Using optimally wide channels in 802.11ac networks has been the topic of various research work. Nevertheless, the efficiency of both Static and Dynamic Multichannel Access methods (SMA and DMA) is a challenging issue, since they employ the Enhanced Distributed Channel Access (EDCA) to provide the Quality of Service (QoS). Indeed, EDCA enables QoS through service differentiation between priority (Voice and Video) and non-priority (Besteffort and Background) traffics. Consequently, the concept of priority may severely starve non-priority traffics from channel access, and lead to an unfair bandwidth allocation. In this paper, we highlight the starvation issue of non-priority traffics in 802.11ac networks. Thereby, we propose a Starvation avoidance DMA (SDMA) method by means of 80 and 160 MHz channel bonding. The individual throughput is measured for comparing SDMA and DMA methods. The obtained results show a significant improvement in throughput of non-priority traffics, while maintaining the throughput level of priority traffics. Graphical abstract: Highlights: Starvation issue of low priority traffic classes in 802.11e quality of service WLANs. Underutilization of channel bonding in 802.11ac very high throughput WLANs. Starvation avoidance through dynamic multichannel access method under 80 and 160 MHz wide channels. A better use of bandwidth by enabling simultaneous transmissions between high and low priority traffics.